Anti-Diphtheric Toxin Antibodies in Healthy Children in Kindergartens Using the Immunoenzymatic Assay Method - Santoso, Hendra; Suwendra, I Putu; Kari, I Komang (Paediatrica Indonesiana, 1990)
Although the immunization program for children in Indonesia follows the WHO recommendation, in some areas high diphtheric morbidity rates still occur for children under 5 years of age. This study deals with the ELISA for immunoglobulin G antibodies against diphtheric toxin in healthy children in kindergartens to determine the immunity status. One hundred and ninety eight samples of serum were collected from children of 18 kindergartens in West, East and South Denpasar districts and were investigated for Ig G diphtheria using the ELISA method. History of immunization was obtained from the patient's immunization cards and an interview by the doctors. It was assumed to be immune when the lg G level was above 0.01 IU/ml. Eighty one out of 95 (85%) children from the control group (who had never had basic immunization) had Ig G levels above 0.01 IU/ml and 81 out of 83 (97.6%) children from the group who had completed basic immunization (3 injections) had Ig G level above 0.01 IU/ml. It seemed that natural infection played still a major role to develop immunity in those children.